IbM KELOMPOK PETERNAK SAPI PERAH Dl BENDUL MERISI KELURAHAN BENDUL MERISI, KECAMATAN WONOCOLO, KOTA SURABAYA - Gunawan, Bambang; Nurlina, Nurlina (University of Merdeka Malang, 2017)
Potential products fresh milk from a partners dairy farmers in the area Bendul Merisi Surabaya is still quite favorable, but the technology has not been used in terms of addressing the problem of livestock waste, so the existence of the business partners still largely very simple in handling the waste, which could impact unhealthy society around. The existence of farm businesses that are geographically dense settlements which are urban areas in Surabaya, where villagers are a mixture of local women for newcomers. Required touch technology and knowledge in the group of dairy farmers are still traditional, thus providing added value to the farm business that is expected to have an impact on the surrounding environment healthier.In the implementation of community service (PPM) is made to partners I, namely Mr. Masoud located in the Bendul Merisi, 27 Surabaya and partners II, Mrs. Aslam in the Bendul Merisi, 31 Surabaya, both within the village RW.6 RT.5 Bendul Merisi Wonocolo Subdistrict Surabaya. Priority issues in general partners after advocacy by Tim PPM states have realized the importance of livestock wastewater treatment so as not to impact negatively on the environment and understand the importance of fresh milk production management by developing a broader market access (internet media).The purpose of this devotion 1). provide a good understanding of the handling of liquid waste from the farm; 2). provide a good understanding of marketing management of fresh dairy products; 3). develop household business partners who are economically independent. The method is offered for problems of waste and management are 1) helping to prepare the handling and management of liquid waste effectively is by building bathtub tiered so that the water coming out of the location of the farm is quite clean and does not pollute the environment, 2) help increase the marketing management product by utilizing Internet access.By the conclusion of 2016 IbM have done the steps are 1) the innovation of science and technology in the form of construction of wastewater treatment basin farms in stages; 2) advocacy to partner in improving the understanding of appropriate technology and 3) to facilitate the implementation of Internet technology to expand its internet blog marketing information and business networks. With these steps, the partners feel the positive benefits such as ease of access to fresh milk sales and the emergence of consciousness and moral responsibility for pollution of river water in view of the farm is located in a densely populated urban environment Surabaya.DOI: https://doi.org/10.26905/abdimas.v2i2.1811